Acquisition or greenfield entry into Africa? Responding to institutional dynamics in an emerging continent. (10th February 2017) - Chen, Ruiyuan; Cui, Lin; Li, Sali; Rolfe, Robert
Abstract : Research Summary: Foreign direct investment establishment mode literature has focused on the impact of unidimensional measures of institutional status, despite that institutional environments in emerging economies undergo substantial and continuous changes in multiple dimensions. This study integrates the dynamic institution‐based view with the theoretical construct of institutional competitive advantages to examine the heterogeneous strategic responses of investing firms to host country institutional dynamics. Empirical results from 2, 245 FDIs into Africa during the period 2008–2013 show that multinational enterprises MNEs are more likely to adopt: (1) a greenfield mode in countries with rapid development of formal institutions; and (2) an acquisition mode in countries with rapid development of factor markets. Moreover, the regional experience of MNEs strengthens the first effect, while the institutional ties strengthen both effects. Managerial summary: The dynamic development of a host country's institutional and factor market conditions is a critical consideration for multinational enterprises when entering emerging countries. By studying 2, 245 foreign direct investments into Africa during the period 2008–2013, we find that MNEs are more likely to enter African countries that have formal institutions that are rapidly improving via greenfield investments. This is especially true for those MNEs with prior investment experience in Africa or with local government connections. We also find that acquisition modes are more likely to be adopted in African countries with rapidly improving factor market conditions, especially by MNEs with local government connections. We promote a dynamic perspective for MNEs for assessing business opportunities and entry modes in Africa. Copyright © 2016 Strategic Management Society.